2019
DOI: 10.1016/j.lindif.2018.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in statistical learning predict children's reading ability in a semi-transparent orthography

Abstract: Learning to read is a milestone in a child's life, and reading ability is a strong predictor of academic outcomes. Some studies have revealed that individual differences in the capacity for implicit statistical learning are linked with children's reading skills in English, which has a deep orthography, but we do not know whether the same relation is found in semi-transparent orthographies such as Norwegian. Additionally, the relative contribution of statistical learning alongside other cognitive measures known… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 76 publications
4
42
0
Order By: Relevance
“…Secondly, the hypothesis also predicts that the statistical learning deficit observed in children with DLD is domain-general and should thus also be present outside the auditory verbal domain. As for the first prediction, there is evidence that in typically developing (TD) children and in children with dyslexia, statistical learning of regularities between non-linguistic elements in the visual domain (e.g., unfamiliar cartoon-like characters, meaningless shapes or symbols) and visuomotor domain (e.g., a sequence of computer screen locations in which a cartoon or shape appears) correlates with reading performance (Arciuli & Simpson, 2012;Hedenius et al, 2013;Steacy et al, 2019;Vakil, Lowe, & Goldfus, 2015;van der Kleij, Groen, Segers, & Verhoeven, 2018;von Koss Torkildsen, Arciuli, & Wie, 2019) and grammar ability (meta-analysis by Hamrick et al, 2017). As for the second prediction, there is also evidence that children with DLD perform worse on statistical learning tasks with non-linguistic stimuli in the visuomotor domain than typically developing children (Lum, Conti-Ramsden, Morgan, & Ullman, 2014).…”
Section: Statistical Learning Outside the Language Domainmentioning
confidence: 98%
“…Secondly, the hypothesis also predicts that the statistical learning deficit observed in children with DLD is domain-general and should thus also be present outside the auditory verbal domain. As for the first prediction, there is evidence that in typically developing (TD) children and in children with dyslexia, statistical learning of regularities between non-linguistic elements in the visual domain (e.g., unfamiliar cartoon-like characters, meaningless shapes or symbols) and visuomotor domain (e.g., a sequence of computer screen locations in which a cartoon or shape appears) correlates with reading performance (Arciuli & Simpson, 2012;Hedenius et al, 2013;Steacy et al, 2019;Vakil, Lowe, & Goldfus, 2015;van der Kleij, Groen, Segers, & Verhoeven, 2018;von Koss Torkildsen, Arciuli, & Wie, 2019) and grammar ability (meta-analysis by Hamrick et al, 2017). As for the second prediction, there is also evidence that children with DLD perform worse on statistical learning tasks with non-linguistic stimuli in the visuomotor domain than typically developing children (Lum, Conti-Ramsden, Morgan, & Ullman, 2014).…”
Section: Statistical Learning Outside the Language Domainmentioning
confidence: 98%
“…A smaller set of studies on ISL and typical reading has demonstrated correlations between ISL abilities and reading skills in first (Arciuli and Simpson, 2012b;e.g., Apfelbaum et al, 2012;Qi et al, 2019;von Koss Torkildsen et al, 2019; but see Schmalz et al, 2019 for contrasting results) and second language (Frost et al, 2013). The majority of these individual differences studies indexed ISL by one non-linguistic visual segmentation task (Arciuli and Simpson, 2012b;Frost et al, 2013;von Koss Torkildsen et al, 2019), yet without the (explicit) assumption that the observed relationship is dependent on the visual presentation modality or the type of input statistics the task of choice taps on. In the theorizing, ISL is typically treated as a unified theoretical construct, a "general capacity for picking up regularities" that is predicted to correlate with measures of literacy (see Siegelman et al, 2017a, for a discussion).…”
Section: Isl Language Acquisition and Readingmentioning
confidence: 99%
“…Individual‐differences studies from recent years confirm this prediction, suggesting that individual SL performance in fact predicts variability in linguistic outcomes. In this vein, individual differences in SL performance among both children and adults were shown to correlate with abilities such as syntactic processing (Kidd, ; Kidd & Arciuli, ; Misyak, Christiansen, & Tomblin, ), lexical knowledge and vocabulary size (Mainela‐Arnold & Evans, ; Shafto, Conway, Field, & Houston, ; Singh, Steven Reznick, & Xuehua, ; Spencer, Kaschak, Jones, & Lonigan, ), speech perception (Conway et al, ; Conway, Karpicke, & Pisoni, ; Lany, Shoaib, Thompson, & Estes, ), and literacy acquisition in first language (Arciuli & Simpson, ; Tong, Leung, & Tong, ; Torkildsen, Arciuli, & Wie, ) as well as second language (Frost, Siegelman, Narkiss, & Afek, ; A. Yu et al, ; see Arciuli, for a review). More direct evidence comes from a handful of longitudinal studies.…”
Section: Introductionmentioning
confidence: 99%